Mismatched Perceptions of Mentors and Pre-Service Teachers in Implementing Warm-Up Activity During Field Teaching Program - Warahma; Azwar Abidin; Suhartini Syukri (AL LUGHAWIYAAT: JOURNAL OF ENGLISH LANGUAGE TEACHING, 2025)
This qualitative study aims to explore the mismatched perceptions of mentors and pre-service teachers in implementing warm-ups during a field teaching program. The study involved four mentor teachers and six pre-service teachers as participants. Through thematic analysis of reflections and in-depth interviews, the study revealed that there are several mismatched perceptions among mentors and pre-service teachers when implementing warm-ups, including time allocation and the benefits of these activities. Mentor teachers consistently advocated for a concise 5-minute warm-up during the opening stage. In contrast, pre-service teachers preferred 10-15 minutes for these activities. This study also identified mentors and pre-service teachers who acknowledged the benefit of these activities. Mentor teachers stated that these benefits include preparing students, stimulating students' thinking, and generating student enthusiasm. Pre-service teachers stated these benefits, including activating prior knowledge, increasing engagement and motivation, facilitating review and reinforcement, fostering communication, and creating a fun and relaxed atmosphere. The findings highlight the importance of balancing the benefits of warm-ups with efficient time management as an optimal approach for opening lessons.